2014
DOI: 10.1021/ol502376e
|View full text |Cite
|
Sign up to set email alerts
|

Rare Streptomyces N-Formyl Amino-salicylamides Inhibit Oncogenic K-Ras

Abstract: During a search for inhibitors of oncogenic K-Ras, we detected two known and two new examples of the rare neoantimycin structure class from a liquid cultivation of Streptomyces orinoci, and reassigned/assigned structures to all based on detailed spectroscopic analysis and microscale C3 Marfey’s and C3 Mosher chemical degradation/derivatization/analysis. SAR investigations inclusive of the biosynthetically related antimycins and respirantin, and synthetic benzoxazolone, documented a unique N-formyl amino-salicy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 26 publications
2
54
0
Order By: Relevance
“…7 However, the exact mode of action and protein targets remain unclear, and there may still be some interplay between the ER and mitochondria, as GRP-78 has been reported to protect epithelial cells from ATP depletion. 44 Consistent with K-Ras acting as a key molecular switch that regulates cell growth, proliferation, and differentiation, studies have demonstrated that preventing Ras PM localization blocks all oncogenic activity, making this family of compounds promising for treating cancer. 127 5.3.4 Inhibition of K-Ras plasma membrane localization.…”
Section: Down-regulation Of Grp-78mentioning
confidence: 98%
See 1 more Smart Citation
“…7 However, the exact mode of action and protein targets remain unclear, and there may still be some interplay between the ER and mitochondria, as GRP-78 has been reported to protect epithelial cells from ATP depletion. 44 Consistent with K-Ras acting as a key molecular switch that regulates cell growth, proliferation, and differentiation, studies have demonstrated that preventing Ras PM localization blocks all oncogenic activity, making this family of compounds promising for treating cancer. 127 5.3.4 Inhibition of K-Ras plasma membrane localization.…”
Section: Down-regulation Of Grp-78mentioning
confidence: 98%
“…5 Spectroscopic data showed its relationship to antimycins A 1 and A 3 and was used to elucidate its structure. 43,44 Several variants of neoantimycins differing in the 3-formamidosalicylate moiety and/or oxidation have also been reported. SNA 15896 (soil, Ibaraki Prefecture, Japan) during screening for immunosuppressants.…”
Section: Antimycin-type Depsipeptides With a 15-membered Macrocyclic mentioning
confidence: 99%
“…Among a set of compounds that displace K-RasG12V but not H-RasG12V from the PM in an HCS (18), we found an oligomycin family and a rare neoantimycin family of Streptomyces-derived molecules and the antidiabetic drug metformin (22)(23)(24)35) (Fig. 1A and B).…”
Section: Ampk Activation Triggers Dissociation Of K-ras From the Pmmentioning
confidence: 99%
“…1A and B). All of these compounds have been reported to inhibit various aspects of mitochondrial function (22)(23)(24)35). Since inhibition of mitochondrial activity depletes cellular ATP levels and activates AMPK (36, 37), we tested whether direct AMPK activation would also mislocalize K-RasG12V.…”
Section: Ampk Activation Triggers Dissociation Of K-ras From the Pmmentioning
confidence: 99%
See 1 more Smart Citation